OUR EXPERIENCE OF SURGICAL TREATMENT FOR CHRONIC PULMONARY THROMBOEMBOLISM - TSUKAGOSHI, Yoshihisa; OHTO, Toshiaki; MASUDA, Masahisa; NIKAIDO, Yoji (Japanese Journal of National Medical Services, 2004)
Chronic pulmonary thromboembolism (CPTE) is one of the causes of pulmonary hypertension and has a poor prognosis. Medical therapy is generally unsatisfactory, and pulmonary thromboendarterectomy (PTE) provides the possibility of a cure. We report our experiences of surgical treatment for CPTE. Between July 2002 and July 2003, 6 patients (5 men, 1 woman) underwent PTE at our hospital. The mean age was 46.8 years (range 20-64). Preoperative pulmonary hemodynamics and gas change data demonstrated pulmonary hypertension and hypoxemia. All patients demonstrated central type disease on CT and pulmonary angiography. We adopted the median sternotomy approach under cardiopulmonary bypass with deep hypothermia and intermittent circulatory arrest. All patients survived, and showed declines in their mean pulmonary arterial pressure (m-PAP) and pulmonary vascular resistance (PVR). Their gas change after one month did not show a significant improvement. PTE is the best procedure in selected patients with CPTE to improve clinical symptoms.